Residency in Anaesthesiology – a current perspective on the Group I Hospital internships - Roxo, Miguel; Paes Mamede, Mónica; Inês; Chen-Xu, José (Journal of the Portuguese Society of Anesthesiology, 2023)
Introduction: The specialty of Anaesthesiology stands for evidence-based practice and meticulous training. In fact, the most recent change to the residency program was the addition of a two months internship at Group I hospitals, which was introduced in January 2020. Material and Methods: A descriptive cross-sectional observational study was carried out based on an online survey with the objective of defining, according to the perception of trainees, the quality, usefulness, and logistical resources of this internship. The survey consisted of 14 questions, divided in two groups: questions related to training and work and questions related to the logistical component of the internship. Results: From a universe of 160 trainees, 75 responses (46.9%) were obtained. Group I internships proved to be an asset for the Anaesthesiology residency. Most of the respondents had a high level of satisfaction with the internship, namely regarding autonomy and variety of functions performed, which culminate in a desire to work in district hospitals in the future. Discussion and Conclusions: This analysis of the first two years of Group I internship may serve as the basis for a wide-ranging discussion that may lead to a process of continuous improvement of the conditions and possible introduction of new elements into an internship that has already shown to be of value.